PERANAN DEWAN ADAT DAYAK (DAD) DALAM MITIGASI KONFLIK TANAH ADAT: (Studi di Dewan Adat Dayak Provinsi Kalimantan Tengah) - Sipty Agustina; Ester Sonya Ulfaritha Lapalu (Jurusan Ilmu Pemerintahan, 2021)
The protection and recognition of indigenous peoples is very important in the dynamics of national and state life in the Indonesian state considering the diversity of its nations consisting of various ethnic groups and the presence of institutions that represent these cultural identities are also very important to strengthen the protection and recognition of elements of the entity. which exists. In particular, one of them is in the Province of Central Kalimantan which has a wealth of customary culture that has its own customary rights and laws that reflect the identity of its indigenous people. The presence of customary institutions based on indigenous peoples has also become the focus of researchers where the Dayak Customary Council of Central Kalimantan Province is present in the midst of the community as a supervisory institution that assists in the development and fight for the rights of indigenous peoples. In this study, the researcher analyzes how the actions or role patterns are carried out by the Dayak Customary Council of Central Kalimantan Province and the factors that influence the role patterns taken by the institution based on the duties and functions of the institution as stipulated in the Central Kalimantan Provincial Regulation No. 16 of 2008 and based on the Decree of the Council. Dayak Adat Central Kalimantan Province No.1 of 2019 concerning the organizational structure of the Dayak Customary Council in Central Kalimantan through the progress of conflict resolution in customary land disputes. The research method uses descriptive qualitative research methods with a research approach using interviews or direct observation of the relevant sources who have credibility with the research object. From the results of the study, it was concluded that the Dayak Customary Council of Central Kalimantan Province carried out or managed conflicts based on Dean & Jeffrey Z.Rubin's theory of conflict mitigation, which tends to provide problem solving patterns with alternatives or instruments through traditional courts. The factor that hinders conflict resolution from the research findings is the existence of political interests with investors, both in the form of profit and power.